Jezus Chrystus jako model dla postaci Apolloniusza z Tiany - Sieradzan, Jacek (Vox Patrum, 2004)
In this short article the author present Jesus Christ of the Gospel as the model for the life of Apollonios of Tyana’s biography by Flavius Filostratos. Author found out 28 analogies in hagiographies of both, and in addition 12 analogies in miracles activity.